Angiofibroma of Soft Tissue on MRI and FDG PET/CT Image. (March 2022) - Xiao, Liu; Yang, Liu; Wang, Yueqi; Li, Lin
Abstract : Abstract: Angiofibroma of soft tissue is a rare benign mesenchymal neoplasm. We reported a case of angiofibroma of soft tissue in a 61-year-old woman. MRI examination indicated a soft tissue mass in the right lower thigh, which showed isosignal intensity on T1-weighted imaging and heterogeneous high signal intensity on T2-weighted imaging. This lesion had intense tracer uptake, with an SUVmax of 7.24 on FDG PET/CT. Our case revealed that when soft tissue masses with intense FDG uptake on PET/CT are encountered, angiofibroma of soft tissue should be considered in the differential diagnosis.